Strategi Perancangan Konten Media Sosial Tiktok dalam Acara SCTV Awards 2023 - Laksono, Lubna Maharani Dewi Alfiona; Sudradjat, Ratih Hasanah; Rozaq, Miftahul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Surya Citra Televisi or SCTV Surya Citra Televisi or SCTV is a television station that has superior programs such as soap operas, FTV, Infotainment, and special events that aim to appreciate community figures who have worked on the SCTV screen. SCTV's social media is an essential aspect of promoting the programs on SCTV. The presence of SCTV social media creates interaction between the @sctv_ account and TikTok users, influencing engagement on the account. Content is essential to increase engagement and achieve target engagement on the Tiktok @sctv_ account. The TikTok account @sctv_ uploads various content to promote programs and gain engagement. One of the content is about the 2023 SCTV Awards program. In designing this work, the author wants to provide insight into the selection and process of creating content to provide a broad reach for TikTok users, especially followers @ sctv_. The theoretical basis used to discuss the design of this work is Marketing Communication, Content, Social Media, The Circular Model of SoMe, TikTok, and Engagement. The data collection methods that the author uses are numbers and narratives, observation, and documentation.